Rationally reduced libraries for combinatorial pathway optimization minimizing experimental effort - Markus Jeschek (Nature Portfolio, 2016)
Rational design in metabolic engineering is often difficult and limited to small screens, favouring construction of compressed smart libraries. Here the authors introduce RedLibs, an algorithm to design combinatorial RBS libraries to allow pathway optimization with minimal experimental resources.